Identification of Oppa Box Msme Problems and Solutions in Padang City - Nila Sari, Vivi; Yelviana, Ade; Fitri, Amelya; Juwagiantoro, Bagus; Anggun Suri, Puti (Universitas Ibn Khaldun, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are a form of productive economy run by the lower middle class. There are various benefits obtained from the MSME sector, including in improving the economy, reducing poverty, providing employment, and culminating in the development of social facilities. But in fact, MSMEs in Indonesia, including Oppa Box Padang MSMEs, still experience various obstacles in development activities, one of which is the issue of business legality. In this case, MSMEs need to adapt so that the problems experienced can be resolved. One of those who needs this adaptation plan is the Oppa Box MSME located on Jalan Aru No. 6 Lubuk Begalung nan XX, Padang City, West Sumatra, 25221, next to Putra Indonesia University YPTK Padang. This community service activity begins with surveys and interviews, mapping and identifying problems, formulating solutions, and implementing mentoring activities. The impact of this activity is the expansion of product marketing and business development of Oppa Box Padang MSME Actors.